2017
DOI: 10.1037/dev0000266
|View full text |Cite
|
Sign up to set email alerts
|

Changes in behavior and salivary cortisol after targeted cognitive training in typical 12-month-old infants.

Abstract: Previous research has suggested that early development may be an optimal period to implement cognitive training interventions, particularly those relating to attention control, a basic ability that is essential for the development of other cognitive skills. In the present study, we administered gaze-contingent training (95 minutes across 2 weeks) targeted at voluntary attention control to a cohort of typical 12-month-old children (N = 24) and sham training to a control group (N = 24). We assessed training effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…All participants viewed a 20‐min stimulus battery consisting of a mixture of dynamic and static viewing materials (Figure ). Of note, this battery constituted the first visit of a repeat‐visit study, the results of which have been presented elsewhere (de Barbaro et al., ; Wass, Cook, & Clackson, ). The present analyses and research questions are completely different to those reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…All participants viewed a 20‐min stimulus battery consisting of a mixture of dynamic and static viewing materials (Figure ). Of note, this battery constituted the first visit of a repeat‐visit study, the results of which have been presented elsewhere (de Barbaro et al., ; Wass, Cook, & Clackson, ). The present analyses and research questions are completely different to those reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…However, the evidence with younger children is still mixed, with some recent studies showing transfer of training to mathematical skills (Jones, Milton, Mostazir, & Adlam, 2019). In addition, the few studies that have been carried out with younger children (Thorell, Lindqvist, Bergman, Bohlin, & Klingberg, 2008;Wass, Cook, & Clackson, 2017;Wass, Porayska-Pomsta, & Johnson, 2011) and with young and diverse samples (Ballieux et al, 2016;Goldin et al, 2014) have showed promising results. Indeed, a meta-analysis of cognitive training studies concluded that training is more likely to lead to far transfer in younger participants than in older participants (Wass, Scerif, & Johnson, 2012), perhaps because the neural networks underpinning executive functions are undifferentiated earlier in development (Karmiloff-Smith, 1998).…”
mentioning
confidence: 99%
“…Firstly, for lower SES children, attendance in lessons is crucial for academic success (Sylva, Melhuish, Sammons, Siraj-Blatchford, & Taggart, 2011), and so it is important that interventions do not take children out of the classroom for extended periods. Secondly, brief cognitive interventions with as few as three sessions have been administered with infants and toddlers and have shown transfer, suggesting that brief training interventions can be effective (Wass et al, 2011(Wass et al, , 2017. Finally, the duration of training has been shown to have little impact on the extent of transfer (Karbach & Verhaeghen, 2014;Melby-Lerv ag et al, 2016;Sala & Gobet, 2017), suggesting that shorter training interventions should be prioritized, as their relative brevity means they are more likely than longer interventions to be widely implemented.…”
mentioning
confidence: 99%
“…These infants may be receiving less external social stress buffering and thus be more likely to experience hyper-arousal, which is known to impede attention functions (Arnsten, 2009). In addition, a prior study using an empirically validated attention training procedure found that infants in the attention training treatment group had lower cortisol at post-test than did infants in the control group (Wass, Cook, & Clackson, 2017). Prior research has also established that maternal support for infant attention through joint attention interactions has direct benefits for sustained attention in infancy (Yu & Smith, 2016).…”
Section: Discussionmentioning
confidence: 99%